PENGARUH PENGALAMAN KERJA, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI PUSKESMAS DASUK KABUPATEN SUMENEP - Ach.Taufik Rahman; Sayekti Suindyah; Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 36 employees. The objectives of this study are 1). To find out and describe the object or research subject at the Puskesmas Dasuk, Sumenep Regency. 2). To test and analyze work experience, supervision and work discipline have a positive and significant effect on employee performance at the Dasuk Public Health Center, Sumenep Regency simultaneously. 3.) To know and analyze work experience, supervision and work discipline partially have a positive and significant effect on employee performance at the Dasuk Public Health Center, Sumenep Regency. The results showed that 1.) Work experience is a measure of the length of time or years of work that the health center employees have taken in understanding the duties of a job and have done it well. Supervision is a process to ensure that organizational goals in the Puskesmas Dasuk management are achieved. Work discipline is an attitude of the willingness and willingness of employees to comply with and obey the norms of work regulations at the Dasuk Puskesmas that apply around them. 2.) Work experience, supervision and work discipline simultaneously have a significant influence on the performance of employees at the Puskesmas Dasuk, Sumenep Regency, proven to be true and the hypothesis is accepted, 3.) Work experience, supervision and work discipline partially have a significant effect on employee performance at the Puskesmas In Sumenep Regency, the truth is proven and the hypothesis is accepted